China’s investments in Africa – The changing landscape - Baliamoune, Mina (2020)
In 2018, Africa attracted US$46 billion in foreign direct investment (FDI). This was an increase of 11% over inward FDI in 2017, defying the global slump in FDI.1 However, this represents only 3.5 percent of the world’s total inward FDI, suggesting that the continent has the potential to attract larger shares of global FDI. China emerged as a major source of FDI to Africa in the early 2000s, and is currently the continent’s main economic partner. While developed nations such as the US and the UK recently turned inward, China dramatically increased its trade and outward FDI destined to African countries over the last several years. FDI from China to Africa increased at 40 percent per annum over the period from 2000 to date.2 Through its investment activities in the continent, China could significantly contribute to the creation of a more investment-friendly environment, especially in developing infrastructure, strengthening upstream and downstream industry linkages, and upgrading skills. Yet, China’s presence in Africa has often been viewed as problematic, especially by observers in Western economies. However, evidence uncovered by recent studies points to significant changes in the Chinese FDI landscape in Africa. These studies generally find that Chinese outward FDI in Africa is increasingly diverse and more complex. The patterns of Chinese investments in Africa are shifting. For example, projects are increasingly undertaken by private enterprises rather than SOEs. Thus, claims that Chinese FDI activities negatively impact the African recipients seem for the most part to be greatly exaggerated or wholly invalid.